Penerapan Sistem Informasi Penjualan Dessert Berbasis Web dengan Pendekatan POAC - Danu Abilsyah Aimar; Tantry Hidayati Sinaga (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The development of digital technology has driven transformation across various sectors, including the food and beverage industry. Dessert businesses face challenges in improving operational efficiency and competitiveness in the digital market. One possible solution is the use of websites as marketing and sales platforms. However, without proper management methods, the utilization of this technology will not be optimal. Therefore, this study applies the POAC (Planning, Organizing, Actuating, Controlling) method to develop a website- based dessert sales system aimed at enhancing business efficiency and customer satisfaction. This study employs a descriptive approach with the POAC method in website-based marketing strategies. The planningphase involves designing e-commerce features, such as product catalogs, an online ordering system, and digital payments. The organizing phase focuses on resource management and technology integration, while actuating includes implementing the system using MySQL, PHP, and CodeIgniter. The controlling phase is conducted through system testing using the Blackbox Testing method to evaluate application performance. The study results indicate that implementing the POAC method in a website- based system enhances the operational efficiency of dessert businesses. Transaction records become more accurate, customers can easily access product information, and the digital payment system improves transaction convenience. Furthermore, the website enables businesses to reach a broader market without geographical limitations. The implementation of the POAC method in website-based business management has proven to improve marketing and sales effectiveness. With a more structured system, businesses can better adapt to market changes and enhance customer interactions. This digital-based strategy also opens new opportunities for developing the culinary business in the modern era.